1980
DOI: 10.1073/pnas.77.10.5975
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of insulin receptors: evidence for involvement of an endocytotic internalization pathway.

Abstract: Recent reports suggest that, after initial cell surface binding, insulin receptor complexes are internalized by absorptive endocytosis (1, 2). Following this, insulin is degraded at one or more intracellular sites, possibly involving lysosomes (3-7). The fate of the internalized receptor is unknown at present, although it is most likely degraded or recycled back to the plasma membrane or both. Gavin et al. (8) were the first to report that insulin could mediate the regulation of its own receptors; they found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

1981
1981
1987
1987

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 23 publications
0
31
1
Order By: Relevance
“…Although the reason for this inhibition is not clear from the current studies, the same phenomenon has been observed in cultured human fibroblasts (21). The quantitative accumulation of intracellular receptors in the presence of chloroquine makes it unlikely that this agent simply inhibits receptor internalization.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Although the reason for this inhibition is not clear from the current studies, the same phenomenon has been observed in cultured human fibroblasts (21). The quantitative accumulation of intracellular receptors in the presence of chloroquine makes it unlikely that this agent simply inhibits receptor internalization.…”
Section: Discussionmentioning
confidence: 54%
“…It is also well established that, after binding to cell-surface recepCell Biology: Green tors, the insulin molecule is internalized and is processed and degraded intracellularly (13)(14)(15)(16)(17)(18)(19). We (21,22) and others (20) have suggested that receptor loss and hormone internalization are related and that insulin is internalized along with its receptor, thus initiating receptor loss or down-regulation. Although indirect evidence exists to support this notion, direct evidence demonstrating insulin-induced internalization of the insulin receptor has been lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, later work from the same laboratory indicates that some inhibitors of transglutaminase were without effect on epidermal growth factor endocytosis, suggesting that epidermal growth factor and a2-macroglobulin do not share the same pathway of internalization, despite occupying the same vesicles (23). Although insulin internalization has recently been linked to transglutaminase activity in human fibroblasts, it was found not to be important in IM-9 lymphocytes (24). Several reports also suggest that the internalization process may be of little significance in mediating insulin action in adipose tissue.…”
Section: Resultsmentioning
confidence: 99%
“…The internalization leads to a concomitant decrease in cell surface receptors. This is also well documented for the insulin receptor (Baldwin et al, 1980). Agonist-induced endocytosis would explain early adenylate cyclase desensitization to 3-adrenergic agonists, since the receptors would be present in endocytotic vesicles but not accessible to signals from outside.…”
Section: Introductionmentioning
confidence: 97%